PENGGUNAAN METODE USER EXPERIENCE QUESTIONNAIRE UNTUK MENGANALISIS KUALITAS PENGALAMAN PENGGUNA APLIKASI MYINDIHOME MOBILE - Karina Karina; Desi Pibriana (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2023)
PT Telkom is a telecommunications service provider company in Indonesia that implements a customer-oriented business and operational strategy. One of the products offered by Telkom is IndiHome. IndiHome provides an application that can be used by customers to carry out all activities related to services to customers known as myIndiHome based on mobile. The facts were found through interviews with PT Telkom employees in the service department and pre-research questionnaires, some customers felt that the myIndiHome mobile application was difficult to use, boring, and not efficient. Then a user experience analysis was carried out to find out from the user's point of view the myIndiHome mobile application and it is hoped that it can provide benefits in the form of recommendations for improvements to improve the quality of the application. User experience analysis was carried out using the User Experience Questionnaire (UEQ) method. The measuring tool at UEQ uses Data Analysis Tools version 11 in excel format. The sample used in this study was 334 respondents using the myIndiHome mobile application in the city of Palembang. The results show that the Mean and Variance values get positive evaluations for all scales, whereas when compared with the dataset, the benchmark results show that there are three scales (attractiveness, precision, and stimulation) that get Above Average results while the other three scales (clarity, efficiency, and novelty) get Below Average results.